2006
DOI: 10.1111/j.1365-2966.2006.10066.x
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of clustering on galaxy properties

Abstract: (abridged)We use a sample of ~200,000 galaxies drawn from the Sloan Digital Sky Survey to study how clustering depends on properties such as stellar mass (M*), colour (g-r), 4000A break strength (D4000), concentration index (C), and stellar surface mass density (\mu_*). We find that more massive galaxies cluster more strongly than less massive galaxies, with the difference increasing above the characteristic stellar mass of the Schechter mass function. When divided by physical quantities, galaxies with redder … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
462
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(509 citation statements)
references
References 63 publications
45
462
2
Order By: Relevance
“…In particular, it has been found that more luminous and massive galaxies are more strongly clustered than fainter and less massive ones (Davis & Geller 1976;Davis et al 1988;Hamilton 1988;Loveday et al 1995;Benoist et al 1996;Guzzo et al 1997Guzzo et al , 2000Norberg et al 2001Norberg et al , 2002Zehavi et al 2002Zehavi et al , 2005Zehavi et al , 2011Brown et al 2003;Abbas & Sheth 2006;Li et al 2006;Swanson et al 2008;Ross et al 2011;Guo et al 2013;Marulli et al 2013); similar trends have been found also as a function of morphology and colours, for which galaxies with a rounder shape and redder show an enhanced clustering. The 2PCF is also often used to provide constraints on galaxy bias b, which quantifies the excess in clustering of the selected sample with respect to the underlying dark matter; however, these estimates have to assume a fiducial cosmology, and are degenerate with the amplitude of linear matter density fluctuations quantified at 8 h −1 Mpc , σ 8 , of the assumed model.…”
Section: Introductionsupporting
confidence: 53%
“…In particular, it has been found that more luminous and massive galaxies are more strongly clustered than fainter and less massive ones (Davis & Geller 1976;Davis et al 1988;Hamilton 1988;Loveday et al 1995;Benoist et al 1996;Guzzo et al 1997Guzzo et al , 2000Norberg et al 2001Norberg et al , 2002Zehavi et al 2002Zehavi et al , 2005Zehavi et al , 2011Brown et al 2003;Abbas & Sheth 2006;Li et al 2006;Swanson et al 2008;Ross et al 2011;Guo et al 2013;Marulli et al 2013); similar trends have been found also as a function of morphology and colours, for which galaxies with a rounder shape and redder show an enhanced clustering. The 2PCF is also often used to provide constraints on galaxy bias b, which quantifies the excess in clustering of the selected sample with respect to the underlying dark matter; however, these estimates have to assume a fiducial cosmology, and are degenerate with the amplitude of linear matter density fluctuations quantified at 8 h −1 Mpc , σ 8 , of the assumed model.…”
Section: Introductionsupporting
confidence: 53%
“…The dependence of galaxy clustering as a function of various intrinsic galaxy properties has been well determined by observations(e.g, Norberg et al 2002;Li et al 2006;Farrow et al 2015;Shi et al 2016). However, in galaxy formation models it is still difficult to reproduce the amplitude of correlation functions for low mass galaxies and on small scales (Guo et al 2011;Wang et al 2012;Campbell et al 2015).…”
Section: Galaxy Correlation Functionmentioning
confidence: 95%
“…Error bars are from bootstrapping simulation data (Barrow et al 1984). The circles with error bars show the SDSS DR7 results (Li et al 2006;Guo et al 2011). 2013; Gonzalez-Perez et al 2014). This reduces the inferred abundance at both low and high stellar masses, and smooths the bump near the "knee" of the function.…”
Section: Present Day Stellar Mass and Luminosity Functionsmentioning
confidence: 99%
“…For example, first taking the spectroscopic based work, Li et al (2006) presented the measured mass dependence of galaxy clustering at z < 0.3 using SDSS data, showing an increase in clustering with mass, which became more pronounced above M * . Moving to higher redshifts, Meneux et al (2008Meneux et al ( , 2009) measured the clustering of mass-selected samples in the VVDS-Deep and zCOSMOS Surveys respectively, finding a clustering mass dependence in their results at redshifts up to z ≈ 1.2.…”
Section: Introductionmentioning
confidence: 99%